PENDIDIKAN KESEHATAN DENGAN MEDIA VIDEO TENTANG KANKER PAYUDARA BERPENGARUH TERHADAP PENGETAHUAN PENCEGAHAN KANKER PAYUDARA - Sri Nur Hartiningsih; Andri Setyorini (STIK SITI KHADIJAH, 2025)
Introduction : Breast cancer is the most common cancer among women in the world. Currently breast cancer is the second cause of death after uterine cancer. In Indonesia, more than 80% of patients come to the hospital with conditions at an advanced stage, so healing is very difficult. Young women are not guaranteed to be safe from breast cancer, so there is a need for knowledge about early detection in young women, especially teenagers. Objective : this study aims to determine the effect of health education using video media about breast cancer on knowledge of breast cancer prevention. Research Metode : this research is quantitative research with pre experimentdesign. Sampling used a total sampling thechique with a total of 25 people. The instrument used as a knowledge questionnaire. The analysis test used is the paired t test. Result and Discussion : The results of this study show that there is an increase in scores with a mean knowledge value of 9 and has a standard deviation of ±45,16 with a p value = 0,000 (p value < 0,05), so the results of this study show that there is a influence of health education with video media abaout breast cancer on adolescent knowledge at SMAN 5 Puspanegara, Yogyakarta. Conclusion : The Influence of health education using video media about breast cancer on knowledge of breast cancer prevention among adolescents at SMAN 5 Puspanegara Yogykarta. Suggestion : Health workers are advised to regulary carry out health education in order to increase knowledge and prevention efforts among adolescents in preventing breast cancer.